A novel method to evaluate prethawing viability of cryopreserved CD34+ hematopoietic stem cells for autologous transplantation. Issue 7 (2nd June 2020) - Marinelli Busilacchi, Elena; Costantini, Andrea; Mancini, Giorgia; Bencivenga, Rossella; Olivieri, Jacopo; Battaglini, Giovanna; Velletri, Laura; Viola, Nadia; Butini, Luca; Capelli, Debora; Poloni, Antonella; Olivieri, Attilio
Abstract : BACKGROUND: Cryopreservation of CD34+ hematopoietic stem cells (HSCs) is associated with variable loss of viability. Although postfreezing CD34+ cell viability can be assessed on the sampling tube (bag tail) directly connected to the main bag (mother bag), results often underestimate the actual viability observed when the mother bag is thawed and reinfused. We assessed a novel method to measure postfreezing CD34+ cell viability, based on small bag (minibag) samples; results were compared with those obtained on the corresponding mother bags and bag tails. STUDY DESIGN AND METHODS: Sixty‐one apheresis procedures of 42 patients undergoing autologous HSC transplant were analyzed. Viable CD34+ cells were quantified with flow cytometry before controlled rate freezing (ICE‐CUBE14M system, SY‐LAB‐ IceCube, SIAD), after 10 days of storage (mini‐bag and bag tail), and before reinfusion (aliquot from a thawed mother bag). Results were compared using Studentʼs t test and Spearmanʼs rho correlation test. RESULTS: The mean CD34+ cell viability before cryopreservation was 99.3% (confidence interval [CI], 98.94‐99.65%); the mean amount of CD34+ cells, white blood cells and neutrophils in the mother bag was 0.8 ± 1.1 × 10 9 /L, 63.4 ± 23.5 × 10 9 /L, and 25.7 ± 15.5 × 10 9 /L, respectively. Mother bags postthawing CD34+ cell viability was 72.3% (CI, 67.74‐76.85%; p < 0.01 compared to prefreezing); no difference was observed with respect to minibags (73.7%; CI, 69.80‐77.59%; p = NS), whereas significantly lower values were found for bag tails (58.6%; CI, 54.19‐63.00%; p < 0.01 vs. both mini‐ and mother bags). CONCLUSION: Compared to bag tails, minibags represent a more accurate tool to measure the CD34+ cell viability of the apheresis mother bag prior to reinfusion; in addition, minibags may could be of help for case‐by‐case calculation of the amount of apheresis to be infused to patients undergoing autologous HSC transplant.